2020
DOI: 10.1091/mbc.e20-04-0237-t
|View full text |Cite
|
Sign up to set email alerts
|

Kinetochore proteins suppress neuronal microtubule dynamics and promote dendrite regeneration

Abstract: Kinetochores connect centromeric chromatin to spindle microtubules during mitosis. Neurons are post-mitotic, so it was surprising to identify transcripts of structural kinetochore (KT) proteins and regulatory chromosome passenger complex (CPC) and spindle assembly checkpoint (SAC) proteins in Drosophila neurons after dendrite injury. To test whether these proteins function during dendrite regeneration, post-mitotic RNAi was performed and dendrites or axons were removed using laser microsurgery. Reduction of KT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 70 publications
4
18
0
Order By: Relevance
“…This result is in agreement with earlier works that have shown that 3-way junctions represent the minimal energy shape for connecting tubular membrane surfaces [64]. Yet, the observed junction geometry may also be influenced by a local effect of cytoskeletal proteins or membrane coating proteins [65][66][67][68][69][70]. Our findings can therefore serve as a basis for further study of the physical mechanism for stabilization of PVD junctions.…”
Section: Three-way Symmetry Of Pvd Junctions Generates Orthogonal Treessupporting
confidence: 92%
“…This result is in agreement with earlier works that have shown that 3-way junctions represent the minimal energy shape for connecting tubular membrane surfaces [64]. Yet, the observed junction geometry may also be influenced by a local effect of cytoskeletal proteins or membrane coating proteins [65][66][67][68][69][70]. Our findings can therefore serve as a basis for further study of the physical mechanism for stabilization of PVD junctions.…”
Section: Three-way Symmetry Of Pvd Junctions Generates Orthogonal Treessupporting
confidence: 92%
“…For example, Atx2 has been previously indicated in actin regulation in the germline ( Satterfield et al., 2002 ) and microtubule organization in mitosis ( Gnazzo et al., 2016 ; Stubenvoll et al., 2016 ). Collectively, these observations are of note because there are strong parallels between the organization of the cytoskeleton in mitosis and in neurons ( Del Castillo et al., 2020 ; Cheerambathur et al., 2019 ; Hertzler et al., 2020 ; Lin et al., 2012 ; Norkett et al., 2020 ; Zhao et al., 2019 ). In mitosis, the cytoskeleton must be reorganized to facilitate chromosome separation and actin ring contraction ( Basant and Glotzer, 2018 ; Mishima et al., 2002 ).…”
Section: Introductionmentioning
confidence: 85%
“…For example, Atx2 has been previously indicated in actin regulation in the germline (Satterfield et al, 2002) and microtubule organization in mitosis (Gnazzo et al, 2016;Stubenvoll et al, 2016). Collectively, these observations are of note because there are strong parallels between organization of the cytoskeleton in mitosis and in neurons (Del Castillo et al, 2020;Cheerambathur et al, 2019;Hertzler et al, 2020;Lin et al, 2012;Norkett et al, 2020;Zhao et al, 2019). In mitosis, the cytoskeleton must be reorganized to facilitate chromosome separation and actin ring contraction (Basant and Glotzer, 2018;Mishima et al, 2002).…”
Section: Introductionmentioning
confidence: 87%